Analisis Penggunaan Uang Elektronik Pada Mahasiswa Fakultas Ekonomi Universitas Negeri Malang (Studi Kasus: Uang Elektronik Brizzi) - Didin Elok Parastiti; Imam Mukhlis; Agung Haryono (Universitas Negeri Malang, 2015)
This research aimed to describe the interest of students on the use of BRIZZI electronic money. This research is qualitative descriptive by using case study method or approach. The results showed that integrated KTM (Student Identity Card) does not increase the use of BRIZZI electronic money among students. Interest of students on the use of BRIZZI electronic money as a means of payment is still very low.Keywords : electronic money, interest of usage, BRIZZI